Airway Epithelium Interactions with Aeroallergens: Role of Secreted Cytokines and Chemokines in Innate Immunity - Gandhi, Vivek D. (Front Immunol, 2015)
Airway epithelial cells are the first line of defense against the constituents of the inhaled air, which include allergens, pathogens, pollutants, and toxic compounds. The epithelium not only prevents the penetration of these foreign substances into the interstitium, but also senses their presence and informs the organism’s immune system of the impending assault. The epithelium accomplishes the latter through the release of inflammatory cytokines and chemokines that recruit and activate innate immune cells at the site of assault. These epithelial responses aim to eliminate the inhaled foreign substances and minimize their detrimental effects to the organism. Quite frequently, however, the innate immune responses of the epithelium to inhaled substances lead to chronic and high level release of pro-inflammatory mediators that may mediate the lung pathology seen in asthma. The interactions of airway epithelial cells with allergens will be discussed with particular focus on interactions-mediated epithelial release of cytokines and chemokines and their role in the immune response. As pollutants are other major constituents of inhaled air, we will also discuss how pollutants may alter the responses of airway epithelial cells to allergens.